Multi‐institutional phase II study of neoadjuvant irinotecan and nedaplatin followed by radical hysterectomy and the adjuvant chemotherapy for locally advanced, bulky uterine cervical cancer: A Kansai Clinical Oncology Group study (KCOG‐G1201). Issue 3 (21st December 2018) - Mori, Taisuke; Makino, Hiroshi; Okubo, Tomoharu; Fujiwara, Yoichiro; Sawada, Morio; Kuroboshi, Haruo; Tsubamoto, Hiroshi; Murakoshi, Homare; Motohashi, Takashi; Kitawaki, Jo; Ito, Kimihiko
Abstract: Aim: A multi‐institutional phase II trial was conducted to determine the efficacy and toxicity of neoadjuvant chemotherapy with irinotecan and nedaplatin followed by radical hysterectomy and adjuvant chemotherapy for locally advanced, bulky stage IB2‐IIB cervical cancer. Methods: Patients with International Federation of Gynecology and Obstetrics (FIGO) stage IB2‐II, bulky type (>4 cm in diameter) squamous cell carcinoma of the uterine cervix were enrolled. Irinotecan (60 mg/m 2 ) was administered intravenously on days 1 and 8 and nedaplatin (80 mg/m 2 ) was also administered on day 1 of every 21‐day cycle. After two cycles of chemotherapy, a radical hysterectomy was performed. Until 6 weeks after the surgery, three to five cycles of the regimen were added as adjuvant chemotherapy. The primary endpoint was the 2‐year relapse‐free survival rate. The response rates and toxicities were evaluated as secondary endpoints. Results: Thirty‐two patients from seven institutions were enrolled in this study. The median age was 48 years (range 25–75 years). The average follow‐up period was 37.8 months (15–71 months). Twenty‐three patients completed the regimen as planned. The objective response rate (complete response + partial response) for the neoadjuvant chemotherapy regimen was 81.2%. The 2‐year and 5‐year relapse‐free‐survival rates were 87.5% and 78.8%, respectively. The incidence of grade 3/4 neutropenia was 6.3% and 34.4% during neoadjuvant and adjuvant treatment, respectively. All other toxicities were well tolerated. Conclusion: Our treatment showed efficacy and tolerability for patients with locally advanced, bulky stage IB2‐IIB cervical cancer. This suggests that treatment has the potential to improve the prognosis compared to concurrent chemo‐radiotherapy.